Mrs. Watson wants your teeth - McGhee, Alison, 1960-; Bliss, Harry, 1964- (Orlando, Fla. : Harcourt, 2004)
A first grader is frightened on her first day of school after hearing a rumor that her teacher is a 300-year-old alien with a purple tongue who steals baby teeth from her students.
Ages 4-7.
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection.
Keywords: Schools -- Fiction; First day of school -- Fiction; Teachers -- Fiction; Teeth -- Fiction; Schools -- Juvenile fiction; First day of school -- Juvenile fiction; Teachers -- Juvenile fiction; Teeth -- Juvenile fiction